Edukasi Dampak Positif & Negatif Peggunaan Smartphone Bagi Santri TPQ Masjid Nurul Ihsan Alai Kota Padang - Wijaya, Anggi Hadi; Syamsi, Syamsi; Ipriadi, Ipriadi (CV. ITTC INDONESIA, 2024)
Advances in technology and information have experienced rapid development in the current era. Smartphones are a form of technological device progress that is easy, practical, and has many functions, namely as a means of communication, a source of information, social networking, a tool for accessing the internet. It's no secret that today's children are exposed to smartphones at a very young age. young. While some people believe that this can be beneficial for their development, there are also those who think that it can be detrimental. Smartphones can provide many benefits for children, For example, they can help improve their cognitive skills and hand-eye coordination. They can also learn new things and get to know different cultures through the use of applications and the internet. However, there is also a risk of children becoming too dependent on smartphones. This is why it is important for parents to monitor children's Smartphone usage and ensure that they use it well and correctly. In this case, students at the TPQ Nurul Ihsan Alai Mosque in Padang City need to be given information about the positive and negative impacts of using smartphones.